2016
DOI: 10.7860/jcdr/2016/20362.8683
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer with Synchronous Renal Cell Carcinoma: A Rare Presentation

Abstract: A 45-year-old female patient presented to Department of Surgical Oncology with chief complaints of pain abdomen and loss of appetite for last six months which was relieved on oral analgesics. There is no relevant past or family history. Clinically per abdomen and pelvic examination was normal. During general examination we found 2x2 cm mobile, hard lymph node in right axilla and the ipsilateral breast showed 8x6cm mobile lump in upper outer quadrant. Contra lateral breast and axilla were normal. Considering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Although many studies have been performed regarding MPCs, these have usually taken the form of case reports [ 11 12 13 ]. There have been several analytic clinical studies on MPCs, but few analytic clinical studies related to breast cancer with MPCs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have been performed regarding MPCs, these have usually taken the form of case reports [ 11 12 13 ]. There have been several analytic clinical studies on MPCs, but few analytic clinical studies related to breast cancer with MPCs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Kurlekar U A et al reported a case of unilateral infiltrating lobular carcinoma of breast and clear cell renal carcinoma which was non reactive for estrogen and progesterone receptors . Ravi Arjunan et al [9] also reported a case of Infiltrating ductal carcinoma of breast with papillary RCC which was non reactive for estrogen and progesterone receptor analysis. Renal cell carcinoma can be seen with other malignancies such as colorectal carcinoma, gynaecological malignancies, lung ,nasopharyngeal and haematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer in the prostate, bladder, lung, breast, colon and rectal cancer, malignant melanomas (MM) and non-Hodgkin's lymphomas (NHL) are the most common malignancies associated with RCC [2]. Arjunan et al reported a rare case of synchronous presentation of carcinoma breast with RCC [7].…”
Section: Discussionmentioning
confidence: 99%